Quality and its impact on efficiency - Cinzia Daraio; Léopold Simar; Paul W. Wilson (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2019)
The issue of quality and its relationship with efficiency and performance is a crucial operational issue in many fields of study including production economics, operations research, engineering and business management. In this paper we provide a methodology for identifying latent quality factors, estimate their statistical significance and analyze their impact on the performance of the production process. This methodology is based on up-to-date computational methods and statistical tests for directional distances. We illustrate the approach using real data to evaluate the performance of European Universities.
Keywords: C1; C14; C13; 330; Nonparametric efficiency; performance assessment; quality; benchmarking; directional distances; conditional efficiency; observed and unobserved heterogeneity; separability condition; European universities